The Effect of a Computerized Early Intervention Program on Developing Social Communication Skills for Children with Disabilities - AlQawod, Ghada Awwad; Al-Dababneh, Kholoud Adeeb (Dirasat: Educational Sciences, 2024)
Objectives: To evaluate the impact of a computer-based early intervention programme on the development of social communication skills in children with impairments. Methods: The study used a single-case study design, with a sample of 5 children with impairments (autism spectrum, intellectual disability) aged 4-6 years who were enrolled in Al-Zarqa Comprehensive Centre for Integrated Day Services. An early intervention programme was established, as well as an 18-item scale for testing social communication skills in children with impairments from the perspective of teachers, to assess the program’s impact. Results: The study’s findings revealed statistically significant differences in the overall score between the pre-measurement and post-measurement of the scale, indicating that the training programme improved social communication skills in children with disabilities. The results also revealed no statistically significant differences in the overall score between the scale’s post-measurement and follow-up measurements, indicating that the program’s effect on social communication skills in children with disabilities in the study sample remained stable. Conclusion: The study recommends strengthening early intervention programs in early childhood with technology and assistive techniques, and developing computer software by taking advantage of the social stories designated for them in children’s literature because of their role in motivating children with disabilities, increasing their level of concentration, and providing the immediate feedback they need to continue. In the educational process, in addition to the need for early intervention programs for children with disabilities to keep pace with the technological development that the world is witnessing in the field of learning and teaching.